Effect of Body Mass Index in Acute Respiratory Distress Syndrome. Issue 6 (December 2016) - Chiumello, D.; Colombo, A.; Algieri, I.; Mietto, C.; Carlesso, E.; Crimella, F.; Cressoni, M.; Quintel, M.; Gattinoni, L.
Abstract : (Abstracted from Br J Anaesth, 116(1):113–121, 2016) A risk factor for any number of associated illnesses and medical complications, obesity definitively has been associated with occurrences of alveolar collapse and hypoxemia. These events have largely been triggered by a tremendous reduction in functional residual capacity, as well as stiffening of lung and chest-wall elastance.